INKUBATOR KREATIF DESIMINASI AUGMENTED REALITY DOLANAN ANAK BERBASIS BUDAYA NUSANTARA - Praheto, Biya Ebi; Barriyah, Insanul Qisti; Sari, Dyan Indah Purnama; Andini, Dinar Westri (Jurnal Berdaya Mandiri, 2024)
The LUKU community is a group of children located in Sarekan Hamlet RT 05, Plembutan, Canden, Jetis, Bantul. Luku itself stands for Put All and Read a 15-minute Book. The children collected in this community are in the age range from early childhood to junior high school. LUKU was formed on the basis of reasons during the COVID-19 pandemic and the home learning policy made children often focused on gadgets and lacked developmental stimulation according to their stage of development. Even though it is the age of these children that the stimulation of creativity is needed. The needs analysis in the LUKU community is that there is a need for developmental stimulation that hones creativity and is also connected to technology (because these children generally have gadgets, but have not been developed optimally according to children's creativity). Therefore, a service program was carried out to stimulate the creativity of the children of the Luku Community through traditional augmented reality-based games. Some of the stages that have been running include socialization, self-learning, and mentoring. The children and parents of the luku community participated in this activity very enthusiastically and always actively participated. Keywords: Creative Incubator, Traditional Games, Augmented Reality